Generating employment and increasing income in agricultural value chains and thereby fostering food security: Case studies of rice and cotton in Benin and Senegal - Ahmadou Aly Mbaye; Assane Bèye; Adama Guèye; Boris Lokonon; Yacor Ndione (University of Bonn, Center for Development Research (ZEF), 2018)
In this paper, we use a case study approach to investigate the patterns of employment and income generation in cotton and rice value chains in Senegal and Benin. The purpose of the paper is to provide a comprehensive description of both value chains in both countries, emphasizing export potential and innovation entry points with the goal of assessing capacity to generate income, create jobs, and bring about food security. To this end, we have combined quantitative and qualitative data to identify direct and indirect value chains' effects on employment and income, paying special attention to vulnerable groups such as youth, women, and informal employees. Surveys data as well as Social Accounting Matrix, have been used to assess the effects of these value chains on employment and income. Our results show strong relationships between value chains and jobs and income patterns.
Keywords: 330; value chains; social accounting matrix; agriculture in Senegal and Benin; rural employment and underemployment; rice and cotton; output and employment multiplier